Age Stereotypes as a Function Of Race - Crew, James C. (Academy of Management Journal, 1984)
The article discusses research pertaining to the effect of race on age stereotyped attitudes. Black and white business students were asked to rate 30-year old and 60-year old workers based on work-related dimensions including performance capacity, potential for development, stability, and interpersonal skills. In the study black students always rated older workers lower than younger workers. The results indicate that black respondents held more extreme age stereotypes than their white counterparts. Experts speculate that the differences may be due to scholastic achievement factors.